Roberto F. Giusti, Poetas de América. Editorial Losada, Buenos Aires, 1956; 149 pp. (Biblioteca contemporánea). - González, Manuel Pedro (El Colegio de México, 1958)
Se reseñó el libro: Poetas de América.